Superior vena cava graft infection in thoracic surgery: a retrospective study of the French EPITHOR database. (6th December 2021) - Filaire, Laura; Mercier, Olaf; Seguin-Givelet, Agathe; Tiffet, Olivier; Falcoz, Pierre Emmanuel; Mordant, Pierre; Brichon, Pierre-Yves; Lacoste, Philippe; Aubert, Axel; Thomas, Pascal; Le Pimpec-Barthes, Françoise; Molnar, Ioana; et al.
Abstract:  : OBJECTIVES: To report our experience on the management of superior vena cava graft infection. METHODS: Between 2001 and 2018, patients with superior vena cava synthetic graft or patch reconstruction after resection of intrathoracic tumours or benign disease were selected retrospectively from the French EPITHOR database and participating thoracic centres. Our study population includes patients with superior vena cava graft infection, defined according to the MAGIC consensus. Superior vena cava synthetic grafts in an empyema or mediastinitis were considered as infected. RESULTS: Of 111 eligible patients, superior vena cava graft infection occurred in 12 (11.9%) patients with a polytetrafluoroethylene graft secondary to contiguous contamination. Management consisted of either conservative treatment with chest tube drainage and antibiotics ( n  = 3) or a surgical graft-sparing strategy ( n  = 9). Recurrence of infection appears in 6 patients. Graft removal was performed in 2 patients among the 5 reoperated patients. The operative mortality rate was 25%. CONCLUSIONS: Superior vena cava graft infection may develop as a surgical site infection secondary to early mediastinitis or empyema. Graft removal is not always mandatory but should be considered in late or recurrent graft infection or in infections caused by aggressive microorganisms (virulent or multidrug resistant bacteria or fungi). Abstract : Surgery extended to the superior vena cava (SVC) for locally advanced non-small-cell lung cancer (NSCLC) or mediastinal tumours (MT) has been shown to have a proven benefit with 5-year survival rates of 36% [1] and 62.5% [2], respectively.